التكافؤ الدينامي ودوره في تحقيق أمانة الترجمة = Dynamic equivalence and its role in achieving translation fidelity - Chik, Abdul Rahman; Chtaibi, Khalid (Universiti Sultan Zainal Abidin (UNIZA), 2023)
Since its inception 2000 years ago, translation fidelity was the most crucial issue. The conception of fidelity before the emergence of dynamic equivalence was far away of the recorded achievements, but as soon as modern linguistic studies appeared at the beginning of the twentieth century, the scales turned, and it became clear that the translation process is deeper as it taught the translator to be a more accurate player when assessing his fidelity. On this basis, the importance of this research consists of shedding light on this most important aspect of the translation system. It concludes that the fidelity of translation in the comprehensive concept: in meaning and significance, fidelity in word, form and impact, is more complicated, based on the fact that equivalence is more difficult task than matching, because trying to achieve equivalence between the original and the translated text forces the translator to monitor the intentions, artistic and creative values in the text, and to match them with others in the translated text, in order to have the same effects that the original text leaves on the recipient, and this depends on the translator, his mastery of both languages, culture, experience and skills.